Mappemonde suivant la projection de Mercator - Jacobs, S.; Fremin, A. R.
This map uses Mercator projection and shows the entire world. Major regions (North and South America, Europe, Asia, Africa, and Australia) are shaded in different colors. Some cities are noted and countries labeled (but not delineated). Bodies of water and other geographic features are marked (with relief shown by hachures).